A Rare Case of Pericardial Effusion in a Patient with Silicosis - Kosuke Saku; Keisuke Yamamoto; Hironori Inoue; Masahiro Ueno (Case Reports in Cardiology)
Silicosis is an occupational lung disorder caused by inhalation of silica dust. It not only causes respiratory disorders but also affects other organs. We report an extremely rare case of silicosis complicated by pericarditis in an 83-year-old male. He had been working as a coal miner and was diagnosed with silicosis at the age of 63. Because he had experienced repeated pericardial effusions, he was referred for a surgical pericardial biopsy to elucidate the cause of his repeated pericardial effusion and to perform pericardial fenestration. Thoracoscopic surgery was performed. The pericardium was resected, and a drain was placed in the left thoracic cavity. Histopathological examination revealed the pericardial degeneration due to silicosis, suggesting that pericarditis and pericardial effusion are related to silicosis. The operation was successful, and he experienced no recurrence of pericardial effusion at the 7-month follow-up.